Distribusi Spasial Dan Struktur Komunitas Plankton Di Daerah Teluk Penerusan, Kabupaten Buleleng - Ni Made Dewi Damayanti; I Gede Hendrawan; Elok Faiqoh (Fakultas Kelautan dan Perikanan Universitas Udayana, 2017)
Research spatial distribution and community structure of plankton in the Penerusan bay has been done on 22 February 2016.Plankton samples were taken at 17 stations using the Horizontal haul. The results obtained by the group of phytoplankton of the most widely found are from class Bacillariophyceae with the abundance of species composition percentage of 77% and the group most zooplankton were found came from class Maxillopoda with the percentage of the species composition of 85%. Highest abundance of phytoplankton found in abundance station 5, while the highest abundance of zooplankton found in abundance station 4. Index values diversity, uniformity and dominance of phytoplankton that is 1,06, 0.40 and 0.11 while the index value of diversity, uniformity and dominance zooplankton are 0.52,0.40 and 0.34. Results of the spatial distribution of phytoplankton abundance scattered in the middle of the bay towards the outside while the spatial distribution of zooplankton abundance spread from the south of the bay towards the middle of the bay and to the north of the bay Forwarding. Water quality in Penerusan Bay of physicists chemical parameters such as temperature obtained ranged from 31.1to 32,5 0C, average brightness obtained 87 %, turbidity obtained ranges between 0,73 to 2.62 ntu, dissolved oxygen (DO) obtained ranged from 6 to 8.3 mg/l , the degree of acidity (pH) obtained ranged from 7.17 to 8.04, salinity obtained ranged from 31-35 ppt, nitrate values obtained ranged from 0.60 to 1.83 mg/l and phosphate values obtained ranged from 0.10 to 0.78 mg/l.